2015
DOI: 10.1136/archdischild-2015-309188
|View full text |Cite
|
Sign up to set email alerts
|

The effects of malnutrition on cardiac function in African children

Abstract: The Effects of Malnutrition on Cardiac Function in African ChildrenJonathan A. Silverman Chair of the Supervisory Committee: Associate Professor Stephen Hawes Department of Epidemiology Objective:To assess the effect of malnutrition on cardiac function in hospitalized African children. Design:Prospective cross-sectional study. Setting:Public referral hospital in Blantyre, Malawi. Patients:We enrolled 272 stable, hospitalized children ages 6-59 months, with and without WHO-defined severe acute malnutrition. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…El-Sayed et al (2006) agreed that cardiac mass index was significantly lower in children with malnutrition, but that left ventricular function was not significantly reduced 16 . The largest and most recent study (Silverman et al 2016) evaluating baseline cardiovascular function in 272 ‘stable’ Malawian children demonstrated no significant differences in cardiac index, stroke volume index and heart rate between inpatient children with and without SAM 25 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…El-Sayed et al (2006) agreed that cardiac mass index was significantly lower in children with malnutrition, but that left ventricular function was not significantly reduced 16 . The largest and most recent study (Silverman et al 2016) evaluating baseline cardiovascular function in 272 ‘stable’ Malawian children demonstrated no significant differences in cardiac index, stroke volume index and heart rate between inpatient children with and without SAM 25 .…”
Section: Discussionmentioning
confidence: 98%
“…Concerns regarding use of intravenous fluids in this vulnerable group of children reference impaired cardiovascular function and susceptibility to overload. A number of studies have been conducted over the last 30 years in Africa, Asia, the Americas and Europe that evaluate cardiovascular function in children with SAM using Echocardiography 16 25 . However, it should be noted that none of these additional studies have been conducted in the context of the child with SAM receiving rehydration therapy, with the exception of the study by Obonyo et al 8 .…”
Section: Discussionmentioning
confidence: 99%
“…However, available evidence suggests that the perturbations of myocardial function are related to complications of sepsis, shock and severe dehydration and not due to ‘heart failure’ 9, 10 . A recent publication by Obonyo et al 2017 demonstrated ‘fluid responsive’ myocardial indices following rehydration in children with SAM and hypovolaemic shock 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations suggest avoiding IV fluids in children with SAM due to concerns about the ability of these children to handle significant volume loads and potential susceptibility to fluid overload and cardiac failure. However, available evidence suggests that the perturbations of myocardial function are related to complications of sepsis, shock and severe dehydration and not due to ‘heart failure’ 9 , 10 . A recent publication by Obonyo et al 2017 demonstrated ‘fluid responsive’ myocardial indices following rehydration in children with SAM and hypovolaemic shock 11 .…”
Section: Introductionmentioning
confidence: 99%